LINEAR REGRESSION MODELS FOR LEFT VENTRICULAR MASS BY ECHOCARDIOGRAPHY IN NORMAL IRAQI SUBJECTS - Al-Kadi, Ramaq Ghassan Wahbi (Al-Nahrain Journal of Science, 2010)
Left ventricular mass (LVM) is an independent risk factor for cardiovascular outcome. M-modeechocardiography, the most commonly used technique for estimation of LVM. The purpose of thisstudy is to establish the regression models for prediction of LVM, measure the normal values of theLVM in normal Iraqi subjects and to compare them with values obtained in Europe, American andArab people.